VARIASI KELOMPOK MAKANAN PENDAMPING AIR SUSU IBU DAN STATUS GIZI ANAK USIA 6-23 BULAN DI KECAMATAN MINGGIR, KABUPATEN SLEMAN, DAERAH ISTIMEWA YOGYAKART - Wulan Ningrum; Th Ninuk Sri Hartini; Tjarono Sari (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2017)
At the age of six months, babies begin to be given complementary foods. The children more than 6 months, should be given extra food. If the child are not have enough about nutrition from complementary foods, it will result in growth disorders and malnutrition. It is the golden period at once critical in the growth process of children, both physical and intelligence.Complementary foods must be come from different food to sufficient the nutritional needs. Good intake will make children have a good nutritional status anyway.Objective to identification of variation complementary food groups and nutritional status of children 6-23 months of age in Minggir.The sample was numbered 194 subjects. Assessment variation views of three components, namely the amount of materials consumed, consumption of breast milk and formula. Variations are grouped into 3, there are lower (grades 0-2.9), intermediate (grades 3 to 3.9), and high (grades 4-5). Variation complementary foods group most a lot on the medium category that is 95 ( 49,0 %) a son as well as nutritional status the most is nutrition good and nutrition more that is 169 ( 87,1 % ). Food intake were assessed by variation complementary foods groups affects the nutritional status of children.The lower variation of complementary foods that will make percentage of malnutrition higher.